2008
DOI: 10.1007/s11829-008-9051-6
|View full text |Cite
|
Sign up to set email alerts
|

Carry-over effects of bumblebee associative learning in changing plant communities leads to increased costs of foraging

Abstract: Flower visitors learn to avoid food-deceptive plants and to prefer rewarding ones by associating floral cues to rewards. As co-occurring plant species have different phenologies, cue-reward associations vary over time. It is not known how these variations affect flower visitors' foraging costs and learning. We trained bumblebees of two colonies to forage in a community of deceptive and rewarding artificial inflorescences whose flower colours were either similar or dissimilar. We then modified the community com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Given that flower foragers appear sensitive to the relative rates of encounter with rewarding and rewardless flowers [47], it is likely that in nature, they do in fact adjust their acceptance thresholds. For example, bumblebees increase their preference for a rewardless flower when a new rewarding flower becomes available and the colour of this new flower resembles the rewardless one but differs from a previously blooming rewarding flower (carry-over effects: [48]). Peak shift, a preference for more easily distinguishable signals [49], might drive foragers to prefer flowers less similar to rewardless ones and therefore to shift acceptance thresholds towards the upper range of rewarding flowers' PDF.…”
Section: (A) Floral Displays and Probability Density Functionsmentioning
confidence: 99%
“…Given that flower foragers appear sensitive to the relative rates of encounter with rewarding and rewardless flowers [47], it is likely that in nature, they do in fact adjust their acceptance thresholds. For example, bumblebees increase their preference for a rewardless flower when a new rewarding flower becomes available and the colour of this new flower resembles the rewardless one but differs from a previously blooming rewarding flower (carry-over effects: [48]). Peak shift, a preference for more easily distinguishable signals [49], might drive foragers to prefer flowers less similar to rewardless ones and therefore to shift acceptance thresholds towards the upper range of rewarding flowers' PDF.…”
Section: (A) Floral Displays and Probability Density Functionsmentioning
confidence: 99%
“…In contrast, learning bears more severe consequences for species engaged in generalized food-deception, which exploit the instinctive expectations of opportunistic pollinators [6] for general floral signals (colour, fragrance and inflorescence shape) [7], but cannot rely on rewarding species to reinforce pollinator associations. Such deceitful species are often pollinated by either inexperienced flower visitors or experienced visitors whose preferred food source has been depleted [7,8], and they commonly experience low visitation and pollination success [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the bumblebee behavior reported in previous experimental studies, where novel rewardless flowers were shown to be visited more frequently when rewarding flowers were depleted (Internicola et al . ).…”
Section: Discussionmentioning
confidence: 97%